Innovative Pedagogical Strategies as a Factor in the Formation of Artistic, Analytical and Communicative Skills of Future Art Teachers - Baranovska, Iryna; Todosiienko, Nataliia; Grab, Oksana (Educological discourse, 2026)
The article examines the conceptual foundations for developing artistic-analytical and communicative skills in future art teachers within the framework of innovative pedagogical strategies. The focus is placed on the changing role of the teacher in the context of sociocultural transformations and digitalisation. The emphasis is laid on the necessity of training professionals capable of conducting in-depth analysis of artistic phenomena, engaging in intercultural dialogue, and ensuring effective communication within the artistic and educational environment. The relevance of pedagogical strategies based on competence-reflective, semiotic-hermeneutic, praxeological, and creative-activity approaches is substantiated. The essence of artistic-analytical and communicative skills is revealed as integral components of professional training, encompassing the intellectual and emotional perception of an artwork, the ability to analyse, reflect, reinterpret creatively, and present results in interpersonal and cultural dialogue. It is shown that artistic-analytical and communicative skills, being interrelated, form a holistic foundation of the professional competence of a future art teacher. They enhance the capacity for dialogical interaction, deep understanding of artworks, and transmission of their meaning and values within the pedagogical process. Innovative methods and tasks aimed at developing these skills, which were implemented in the educational process of the academic programme Primary Education. Art, are presented. Prospects for further research are outlined: the development of a methodological model for integrating innovative pedagogical technologies to activate students’ analytical and communicative activities in art education programs.